(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
This study focusses on investigations based experiments which are carried out to check the mechanical & thermal properties of woven epoxy composite laminates from Basalt/PP, Basalt/PET fibers and vice versa. Fabricated composite samples are subjected to mechanical and thermal characterization. The results reveal that, there is noticeable improvement in mechanical properties with the change of weaves in basalt hybridized composites. Interfacial linkages/bond between fibers and resin cause a significant modulus increase in composites. Thermal behavior of fiber and composite was observed by Thermal Gravimetric Analysis and Differential Scanning Calorimetric. Thermal properties are also affected by hybridization. Thermal conductivity is strongly affected by resin properties. A demonstration of ruptured surface was done by Fractography. The results show that hybridized basalt in different composites leads to a significant improvement in the dynamic and static mechanical properties of composites. Fiber type, weave structure, and resin properties greatly affect the mechanical properties of composites made with hybrid basalt fabrics.